Women's political participation and gender parity in decision-making at all levels in the Caribbean - Bart-Alexander, Karen (ECLAC [Port of Spain]TT, 2007)
Reviews various indicators of women's participation, in government and in the public and private sectors in the English Speaking islands of the Caribbean, Cuba and the Netherlands Antilles. Finds that there has been some improvement both in political participation and in decision making positions but that the improvement is not anywhere near what it is supposed to be because attainment of the 30% quota agreed upon by the Caribbean governments is still sporadic and uncertain.